1977
DOI: 10.3109/10826087709027273
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Indicators of Alcoholism Treatment Outcome

Abstract: This literature review is a systematic attempt to isolate the personal characteristics of alcoholics generally associated with their prognosis. Forty-five studies which met certain standards for inclusion are summarized here. The description of each study and its corresponding list of characteristics of alcoholics investigated for prognostic value are reported in tables. The tables do not reveal stable predictors across the studies, though some personal characteristics are more generally of predictive value th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
2

Year Published

1982
1982
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 48 publications
3
37
1
2
Order By: Relevance
“…Although the effect of the patient's age on posttreatment abstinence has cantly different between the poly-drug abuse and pure alcohol group. No clear trend was noted in the response to been inconsistent in the alcoholism treatment literature, 30 in general younger patients are more prone to recidivism than psycho-social intervention between these two patient groups. The survival of the poly-drug dependent group was signifi-older patients following alcohol dependence treatment.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although the effect of the patient's age on posttreatment abstinence has cantly different between the poly-drug abuse and pure alcohol group. No clear trend was noted in the response to been inconsistent in the alcoholism treatment literature, 30 in general younger patients are more prone to recidivism than psycho-social intervention between these two patient groups. The survival of the poly-drug dependent group was signifi-older patients following alcohol dependence treatment.…”
Section: Discussionmentioning
confidence: 82%
“…30 Conversely, a variety of studies using twin and adoptee cohorts, confirm a significant ance policy was predictive of posttransplantation abstinence. The positive effect that the presence of an active life insur-familial tendency for alcoholism based upon genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schuckit, Schweei, and Gold, (1986) In summarizing 45 studies, using 208 predictor variables, Gibbs and Flannigan (1977) demonstrated that social class and occupation were successful predictors of a favorable outcome of treatment. Bromet, Moos, Wuthman and Bliss, (1977) studied the relationship between a patient's experience in treatment and characteristics of the patient.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Carefully controlled evaluations of treatment generally show less positive results. In fact, "positive findings are indirectly proportional to the amount of experimental control exercised" (Nichols et al, 1979, p. 68 Intelligence Scale (Gibbs & Flanagan, 1977), marital stability, level of education, and number of treatment attempts (Goldfried, 1969). The identification of job stability as a criterion for predicting treatment success 31 may account for the effectiveness of business/industry employee alcoholism programs, some of which claim recovery rates of 65%-75% (Lee, 1976).…”
Section: Dept Of Transportation May 1979) Problem Drinkersmentioning
confidence: 99%